Thermal buckling of flax fibre reinforced epoxy laminated composite plate using finite element analysis. Issue 3 (18th March 2022) - Anandan, Guru; Gopalan, Venkatachalam; Natarajan, Senthilnathan
Abstract: Nowadays natural fibre reinforced composite plates are shown importance due to its eco-friendly nature. If natural fibre reinforced composite is manufactured properly, it will be a suitable replacement for both metallic plates and synthetic fibre reinforced composites. Potential of natural fibres for thermal load still needs a lot of studies. In this work, Flax/epoxy composite plate is prepared and numerical analysis on the thermal buckling of the composite plate is carried out using commercially available Finite Element Analysis software ANSYS Workbench. The design of experiment (DOE) approach is used to examine the buckling characteristics of the composite. The central composite design (CCD) methodology is used for the analysis. The variables considered in the DOE part are aspect ratio, ply orientation, and boundary conditions. Based on the DOE/ANOVA study, quadratic regression equation is developed which relates to the influence of these variables on the critical thermal buckling temperature of the flax/epoxy reinforced composite using Minitab Software.